Kebijakan Perlindungan Profesi Guru PAI Terhadap Tindak Kriminalisasi - khaerudin; Silfiya Agustina; Shinta Ledia; Monik Andriani; Nur Rahma Setyaningrum; Zahra Syifarani; Merza Azanni (Universitas Muhammadiyah Prof Dr Hamka, 2022)
This research examines the problems that often occur in the world of education. The level of criminalization of PAI teachers is very frequent lately. The lack of a firm attitude from the government makes this problem often occur in various regions. It is the duty of the government to minimize the occurrence of criminal acts against teachers. Efforts that can be made at this time are the need for affirmation related to government regulations by developing policies related to legal protection for the teaching profession and disseminating information to the entire community regarding these policies. Becoming a profession as a teacher is a very noble job, which is naturally given a protection or legal umbrella in carrying out his profession as a teacher. The government makes a policy to provide legal protection for a teacher in carrying out his duties as an educator. This is stated in Article 39 of Law Number 14 of 2005 which states that education units are obliged to provide protection to teachers when carrying out their duties. Then the second paragraph of article 39 includes legal protection, professional protection, protection of occupational safety and health. In addition, PAI teachers are also entitled to a legal umbrella in carrying out their duties and responsibilities as well as intellectual rights as stated in Article 14 of this Law. Legal protection for a PAI teacher in carrying out his profession includes acts of violence, then threats, discriminatory treatment, intimidation, or unfair treatment on the part of students, parents of students, and the community.